78.5k views
2 votes
Simplify the expression 5/9 + (-4/5)

User Hyatt
by
4.5k points

2 Answers

0 votes
You must make the denominators equal to each other. (Remember anything you do to the top number you do to the bottom number!! (cross multiply))

- Multiply both 5 and 9 by 5 ( 5/9 turns into 25/45)
- Multiply both -4 and 5 by 9 ( -4/5 turns into -36/ 45)
- Solve as normal for your new problem 25/45 + (-36/45) = -11/45
User Manoj Sehrawat
by
4.6k points
3 votes

Answer:

-11/45

Explanation:

5/9 + (-4/5) =

= 5/9 * 5/5 - 4/5 * 9/9

= 25/45 - 36/45

= -11/45

User Chivas
by
4.8k points